Addressing Long COVID Challenges in South Africa's District Health Clinics: A Scoping Review of Diagnostic Barriers and Care Integration - Dr Kyrtania Pather (International Journal of Infectious Diseases)
Introduction: Long COVID, characterized by persistent symptoms after an initial COVID-19 infection, poses significant challenges in South Africa's public health care system, particularly in district health clinics. These facilities often suffer from resource limitations and high patient loads, making it difficult to effectively diagnose and treat Long COVID. This scoping review investigates the issues of misdiagnosis, under-diagnosis, and systemic barriers within these clinics that impact Long COVID care. Methods: Following PRISMA-ScR guidelines, a scoping review was conducted using academic databases (Cochrane, PubMed, Scopus, and Google Scholar) to examine the impact of Long COVID on public health systems in low- and middle-income countries, with a specific focus on South Africa. The search included terms related to Long COVID, district health care systems, misdiagnosis, and primary care settings. Literature was selected if it addressed diagnostic challenges or health care practices in resource-constrained environments. Studies from 2020 to 2024 were included to ensure relevance to the COVID-19 pandemic context. Data was thematically analysed to uncover patterns and gaps. Results: The initial findings of the review highlights significant barriers faced by district health clinics in diagnosing Long COVID. These include resource constraints, high patient volumes, and the absence of standardized diagnostic protocols. Additionally, the overlap between Long COVID symptoms and those of prevalent conditions like HIV/AIDS and tuberculosis contributes to frequent misdiagnoses. Limited training for healthcare workers in recognising Long COVID further exacerbates the issue of under-diagnosis, and the lack of systematic patient follow-up and comprehensive diagnostic tools may also contribute to care gaps. Discussion: Long COVID is often underrecognized in South Africa's district health clinics, underscoring the need for enhanced awareness, better training for healthcare workers, and the development of standardized diagnostic protocols. Integrating Long COVID management into existing chronic disease frameworks could improve care delivery for affected populations. Addressing these challenges is essential for ensuring accurate diagnoses and equitable treatment within the public health system. Conclusion: This scoping review underscores the major challenges faced by district health clinics in South Africa in managing Long COVID. Addressing resource limitations, improving healthcare worker training, and developing standardized diagnostic pathways are crucial steps toward enhancing Long COVID care. Integrating Long COVID management into existing chronic disease frameworks may offer a viable solution for equitable diagnosis and treatment in the public health sector.